Arranged Marriages among Young Educated Muslim Women in South Sulawesi Indonesia - Alfian, Andi (DINIKA : Academic Journal of Islamic Studies, 2022)
Previous studies claimed that arranged marriages occur in underdeveloped societies, among the uneducated and low social classes. However, in Indonesia, especially South Sulawesi, arranged marriages also occur among young educated Muslim women. This study aims to answer why young educated Muslim women accept arranged marriages by their parents or families instead of marrying their boyfriends. This study also elaborated further on the issue of their feelings and experiences, such as feelings after marriage, dating experiences, and the reasons their parents matched them. This study used a postcolonial approach to analyze why young educated Muslim women accept arranged marriages. By conducting in-depth interviews with five young educated Muslim women who have married through the arranged process, this study found several reasons why young educated Muslim women accept arranged marriages, including the family system, religious teachings, economic considerations, and personal reasons that they consciously choose